Role of Nigella sativa Extract in Reducing the Inflammatory Damage in Oral Submucous Fibrosis - A Review - Hira Batool et al; Mervyn Hosein; Saima Akram Butt; Shafaq Saeed Roghay (ziauddin University, 2024)
Nigella sativa (N. sativa) is an annual flowering plant, which belongs to the family Ranunculaceae. Both the seeds and oil of N. sativa have been researched extensively in the past few years due to the variety of its chemical ingredients and biological properties. N. sativa seeds contain many components including Thymoquinone (TQ), di-thymoquinone, fixed oils, alkaloids, flavonoids, proteins, fatty acids, saponins, and alpha-hederin. TQ is the most pharmacologically active component among all the constituents. The important properties exhibited by TQ are anti-inflammatory, anti-cancer, analgesic, anti-oxidant, anti-hypertensive and anti-diabetic activities. Oral submucous fibrosis (OSMF) is a chronic inflammatory disorder of the oral cavity, which has a multifactorial etiology. Areca nut consumption in the form of quid is considered as the most important factor in the development of the disease. It has a malignant transformation rate of 7-30%. A large number of researches have been conducted to investigate the outcome of using N. sativa and its active constituent TQ in various inflammatory conditions. This article is aimed at reviewing the literature available on various databases (Google Scholar, PubMed, and Online Journals) and to conclude if N. sativa can also be utilized as a potent anti-inflammatory agent for reducing the signs and symptoms of OSMF.   Keywords: Nigella sativa; Oral Submucous Fibrosis; Inflammation.